Potential of Cannabidiol (CBD) to overcome extensively drug-resistant Acinetobacter baumannii - Atchariya Yosboonruang; Anong Kiddee; Achiraya Siriphap; Grissana Pook-In; Chittakun Suwancharoen; Acharaporn Duangjai; Ratsada Praphasawat; Nanthawan Reuk-ngam; Siriwan Nawong; Anchalee Rawangkan (BMC Complementary Medicine and Therapies)
Abstract Extensively drug-resistant (XDR) Acinetobacter baumannii poses a serious clinical challenge due to its resistance to nearly all available antibiotics, including carbapenems and colistin. Cannabidiol (CBD), a non-psychoactive phytochemical from Cannabis sativa L., has recently shown promising antimicrobial activity. This study evaluates the antibacterial and anti-biofilm effects of CBD against XDR A. baumannii isolates and explores its mechanism of action and potential as an adjunct therapeutic agent. Twenty-six A. baumannii isolates collected from ICU medical devices were identified using MALDI-TOF/MS. Antimicrobial susceptibility was assessed by disk diffusion and broth microdilution to determine MICs and MBCs for CBD and standard antibiotics. Synergistic effects were evaluated via checkerboard assays and FICI values. Biofilm inhibition and eradication were assessed using crystal violet and MTT assays. Time-kill studies, membrane integrity assays (DNA/protein leakage, NPN uptake, membrane depolarization), and scanning electron microscopy (SEM) were employed to investigate bactericidal kinetics and membrane-disruptive mechanisms. CBD exhibited activity against antimicrobial resistance isolates (MIC: 3.9 to > 500 µg/mL). Remarkably, CBD synergized with gentamicin, meropenem, and colistin, reducing their effective concentrations by up to 1,000-fold. Combination therapy significantly inhibited and eradicated biofilms. Time-kill assays demonstrated rapid, concentration-dependent killing, with complete bacterial clearance at 4× MIC within 2 h. Mechanistic assays and SEM confirmed that CBD induces extensive membrane damage. These findings highlight CBD’s potential as an effective adjunct to conventional antibiotics for treating XDR A. baumannii infections, offering a novel strategy to counteract antimicrobial resistance.